LC, MSn and LCâMS/MS studies for the characterization of degradation products of amlodipine - Ravi N. Tiwari; Nishit Shah; Vikas Bhalani; Anand Mahajan (Elsevier, 2015)
In the present study, comprehensive stress testing of amlodipine (AM) was carried out according to International Conference on Harmonization (ICH) Q1A(R2) guideline. AM was subjected to acidic, neutral and alkaline hydrolysis, oxidation, photolysis and thermal stress conditions. The drug showed instability in acidic and alkaline conditions, while it remained stable to neutral, oxidative, light and thermal stress. A total of nine degradation products (DPs) were formed from AM, which could be separated by the developed gradient LC method on a C18 column. The products formed under various stress conditions were investigated by LCâMS/MS analysis. The previously developed LC method was suitably modified for LCâMS/MS studies by replacing phosphate buffer with ammonium acetate buffer of the same concentration (pH 5.0). A complete fragmentation pathway of the drug was first established to characterize all the degradation products using LCâMS/MS and multi-stage mass (MSn) fragmentation studies. The obtained mass values were used to study elemental compositions, and the total information helped with the identification of DPs, along with its degradation pathway. Keywords: Amlodipine, LCâMS/MS, Characterization, Degradation pathway